Beyond Dialysis: Reshaping CKD Paradigms in Developing Nations - Ijaz, Muhammad Tayyab; Ijaz, Namra (Journal of the Pakistan Medical Association, 2024)
Dear Sir / Madam, Respected Editor, I am writing to bring attention to the critical need for increased research on conservative kidney management (CKM) in the context of patients with advanced chronic kidney disease (CKD). The recent advancements in developed nations have demonstrated that CKM is a novel and effective approach to caring for CKD patients, particularly those who choose not to pursue maintenance dialysis. Historically, medical care for individuals with CKD has adhered to a paternalistic model, where clinicians make treatment decisions independent of patient preferences. JS Scherer et al observed that a provider’s assessment of a patient’s frailty and response exerted a more substantial influence on the treatment provided than the patient’s comorbidities, functional status, and stated preferences. 2 Furthermore, another study showed that some individuals exhibited a preference for conservative care after shared-decision making, irrespective of the potential survival benefits offered by dialysis if it entailed frequent hospital visits or travel restrictions. 3 This underscores the significance of patient autonomy, where the pursuit of freedom can sometimes outweigh the emphasis on clinical outcomes. However, contemporary CKD management in the 21st century emphasizes shared decision-making and patient empowerment. While research suggests CKM can improve quality of life, reduce hospitalizations, and minimize invasive procedures, offering a valuable alternative to dialysis, its impact on survival becomes less clear for patients over 80 or those with multiple comorbidities.4 Additionally, the inclusion of patients and their families in collaborative decision-making processes has proven advantageous, supported by specialized decision aids that promote well-informed discussions regarding CKM with healthcare providers.5 Nephrologists face significant challenges in implementing effective conservative kidney management (CKM) due to a lack of clinical guidelines, training, evidence, and system-level infrastructure. This has resulted in limited awareness and discussion of CKM among patients and healthcare providers, hindering its adoption. With the global burden of chronic kidney disease (CKD) increasing significantly over the past three decades, particularly affecting low- and middle-income countries, there is a pressing need for innovative, cost-effective solutions. CKM emerges as a viable alternative where dialysis is often inaccessible or unaffordable, with the potential to significantly impact CKD management, especially in resource-limited settings such as Pakistan. I urge the scientific community and policymakers to recognize the importance of supporting and conducting research on conservative kidney management. —Continue